Financial Outcomes in Adolescence and Early Adulthood in Australian Longitudinal Data. (26th February 2020) - de New, John; Ribar, David; Ryan, Christopher; Wong, Clement
Abstract: This article describes and catalogues person‐specific measures of financial outcomes that are available for adolescents and young adults in three large longitudinal Australian surveys: the Longitudinal Surveys of Australian Youth, the Longitudinal Study of Australian Children, and the Household, Income and Labour Dynamics in Australia Survey. It summarises international research that has been conducted on young people's financial outcomes, illustrating outcomes that have been investigated, research questions that have been asked, and distinctions that have been drawn between adolescents and young adults. It considers the strengths and weaknesses of the three surveys for extending this research into the Australian context.